2019
DOI: 10.1002/aur.2087
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological alterations in motor‐auditory predictive coding in autism spectrum disorder

Abstract: The amplitude of the auditory N1 component of the event‐related potential (ERP) is typically attenuated for self‐initiated sounds, compared to sounds with identical acoustic and temporal features that are triggered externally. This effect has been ascribed to internal forward models predicting the sensory consequences of one's own motor actions. The predictive coding account of autistic symptomatology states that individuals with autism spectrum disorder (ASD) have difficulties anticipating upcoming sensory st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 55 publications
(90 reference statements)
0
10
0
Order By: Relevance
“…Here, we found no difference in accuracy of judgement of agency between healthy participants across a range of autism traits, consistent with previous research comparing autistic and healthy participants on similar measures ( David et al, 2008 ; Grainger et al, 2014 ; Russell & Hill, 2001 ; Williams & Happé, 2009 ; Zalla et al, 2015 ). As previously noted by Perrykkad and Hohwy (2020b) and Zalla and Sperduti (2015) , this is in contrast to sense of agency in autism being shown to be reduced under typical experimental paradigms ( Sperduti, Pieron, Leboyer, & Zalla, 2014 ; van Laarhoven, Stekelenburg, Eussen, & Vroomen, 2019 ). Our study also shows no main effects of AQ on other outcomes, except for a negative association with acceleration.…”
Section: Discussionmentioning
confidence: 60%
“…Here, we found no difference in accuracy of judgement of agency between healthy participants across a range of autism traits, consistent with previous research comparing autistic and healthy participants on similar measures ( David et al, 2008 ; Grainger et al, 2014 ; Russell & Hill, 2001 ; Williams & Happé, 2009 ; Zalla et al, 2015 ). As previously noted by Perrykkad and Hohwy (2020b) and Zalla and Sperduti (2015) , this is in contrast to sense of agency in autism being shown to be reduced under typical experimental paradigms ( Sperduti, Pieron, Leboyer, & Zalla, 2014 ; van Laarhoven, Stekelenburg, Eussen, & Vroomen, 2019 ). Our study also shows no main effects of AQ on other outcomes, except for a negative association with acceleration.…”
Section: Discussionmentioning
confidence: 60%
“…van Laarhoven, Stekelenburg, Eussen, and Vroomen [2019] looked at predictions based on self‐action, as measured by evoked EEG response attenuation. The evoked responses of the ASD group were less attenuated by self‐generation than those of the NT group.…”
Section: Resultsmentioning
confidence: 99%
“…Ruiz‐Martínez et al [2020] and van Laarhoven et al [2019] used attenuation of the early component of EEG stimulus‐evoked activity as a measure of prediction. Both showed reduced modulation by prediction of the early ERP response to auditory stimuli in the ASD group compared to the control group.…”
Section: Resultsmentioning
confidence: 99%
“…Recent evidence has shown that self-initiation of tones does not attenuate the auditory N1 in autistic individuals, indicating that autistic individuals may have alterations in anticipating the auditory consequences of their own motor actions ( van Laarhoven et al, 2019 ). The current study extends these findings by demonstrating that the ability to anticipate the sensory consequences of others’ actions may be altered in ASD as well.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that predictive coding might indeed be impaired in autistic individuals ( van Laarhoven et al, 2019 ). In this study, the neural response to self- versus externally initiated tones was examined in a group of autistic individuals and a group of age-matched individuals with typical development (TD).…”
Section: Introductionmentioning
confidence: 99%